Spiritual Leadership Of The Headmaster In Strengthening The Religious Culture Of Nahdlatul Ulama In Mi Islamiyah Wonoplintahan Sidoarjo District - Ningsih, Diah Fitria; Wiyono, Bambang Budi; Timan, Agus (Universitas Negeri Malang, 2024)
The era of moral crisis creates anxiety in society and must be addressed immediately, one of which is through moral education. The head of MI Islamiyah Wonoplintahan has implemented the Nahdlatul Ulama (NU) religious culture with a spiritual leadership style to provide moral education to madrasah residents, especially students, so that they have good morals. This research uses a qualitative approach with a case study type of research. Data collection techniques use interviews, observation and documentation. The research results show the following results: (1) the head of the madrasah has the characteristics of leading with heart, humble, free and empowering, disciplined, respected by those he leads, his work is relaxed and serving, fair, tolerant, spirit of good deeds and honesty; (2) the forms of NU religious culture at MI Islamiyah Wonoplinlahan Sidoarjo, namely istighosah, tahlil, pilgrimage, morning reading of nadhoman books written by NU ulama, Friday blessings on Friday Legi, banjari prayers, dhikr/praise together out loud, and Celebration of Islamic Holidays (PHBI) NU theme; (3) the head of the madrasah in implementing NU religious culture has an important role, namely creating programs, motivating, being an example, and collaborating with student parents and the NU community; (4) the application of NU religious culture with spiritual leadership carried out by the head of the madrasah has the impact of fostering a sense of caring and mutual respect in the madrasah environment, students' attitudes are getting better and Students have memorized the Al-Qur’an and the book, the work ethic and performance of employees is increasing, the response is good from student parents, and and have an impact on the progress of madrasah. Keywords: spiritual leadership; madrasah head; NU religious culture